A new measure of financial constraints applicable to private and public firms - Schauer, Catharina; Elsas, Ralf; Breitkopf, Nikolas (Journal of Banking & Finance, 2019)
We study managers’ self-assessment of their firm’s financial constraint status to assess the validity of commonly used indicators of financial constraints. As categorizations based on common financial constraints measures lead to high misclassifications, we derive a new measure of financial constraints which performs well in-sample and out-of-sample for private firms. Applying our new measure to a large sample of private European firms, we find consistently lower investment-cash flow sensitivities and greater distortions in response to exogenous financing frictions for constrained firms across countries. Besides private firms, our new measure can also be applied to listed U.S. firms, as it reliably identifies constrained firms as measured by the occurrence of liquidity events and the incidence of an inelastic capital supply.